2021
DOI: 10.1055/s-0041-1733781
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood Use for Admission Blood Tests of VLBW Preterm Neonates: A Randomized Control Trial

Abstract: Objective Umbilical cord blood (UCB) for admission laboratories is an approach to decrease anemia risk in very low birth weight (VLBW) neonates. We hypothesized that UCB use results in higher hemoglobin concentration [HgB] around 24 hours of life. Study Design A randomized control trial among VLBW infants whose admission laboratories were drawn from UCB (n = 39) or the infant (n = 41) in three U.S. military NICUs (clinicaltrials.gov#NCT02103296). Results No demographic differences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…We assessed reporting by NIH funding: of the 52 studies funded by the NIH, 35 studies (67%) included race and ethnicity data. Among 68 studies not funded by the NIH, 40 studies (58%) reported race and ethnicity data; the difference between NIH-funded and non-NIH–funded studies was not statistically significant by Pearson χ 2 .…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We assessed reporting by NIH funding: of the 52 studies funded by the NIH, 35 studies (67%) included race and ethnicity data. Among 68 studies not funded by the NIH, 40 studies (58%) reported race and ethnicity data; the difference between NIH-funded and non-NIH–funded studies was not statistically significant by Pearson χ 2 .…”
Section: Resultsmentioning
confidence: 93%
“…We identified 120 studies that were entered into Cochrane CENTRAL 2017 to 2021 and met our inclusion criteria (eFigure 1 in Supplement 1). There was a range in the articles’ availability via electronic publication (2016-2021) and publication year (2017-2023).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations